Pengaruh Quality Control dan Lead Time terhadap aktivitas Inbound logistik pada Pt. Syngenta Indonesia Gp Site - Okin Ringan Purba; Sinatria Pandu (CV. Syntax Corporation Indonesia, 2022)
The Quality Control Division plays an important role in Inbound and production activities by ensuring that incoming goods are received in the form of raw materials properly without any defects or called zero defects. Relevant previous research is one of the supports that can be used as a key for the research to be started. In this study, the previous research variables used as a reference are Quality Control, Lead-time, and Inbound Activities. In the midst of very tight competition between companies, it is influenced by competent Human Resources so that the company's productivity remains stable and even increases and can achieve the company's own goals. The method used in this study is a quantitative research method. The sample of this study were 40 respondents, employees of PT. Syngenta Indonesia production and operations division. The results showed that Quality Control had a positive and significant effect on inbound logistics activities and the Lead Time variable also had a positive and significant effect on inbound logistics activities. It can be concluded that the applied quality control process has proven to have a positive effect on the activities of receiving and delivering goods to PT. Syngenta Indonesia GP Site through the dimensions of material control, process control, finished product inspection.